Syllabus: Beyond Quality of Life: Exploring Disability and Bioethics - Schilling, Carol; Blankmeyer Burke, Teresa (Disability Studies Quarterly, 2015)
The syllabus for "Beyond Quality of Life: Exploring Disability and Bioethics" was designed for the Master of Bioethics program at the University of Pennsylvania. This first course on disability for the program conducted an inquiry into bioethical responses to human variations that become categorized as disability. The interdisciplinary project of disability studies provided a fresh theoretical and practical lens through which to view bioethics, its philosophical framework, and the library of cases concerning disability that are argued within that frame.